Achieving zero hunger through women empowerment approaches in agriculture - Ponnusamy, K.; Chakravarty, Ritu (Indian Farming, 2018)
There is no dearth of gender sensitive models in technology transfer. But mostly, they are in the conceptualization stage or scattered testing in some laces or else end up with completion of projects and fewer publications consequently. The models are not upscaled due to lack of support from policy and political angles. The stakeholders in the process of development understood the role of women in building astrong and vibrant agriculture in the rural areas which can alleviate the poverty, malnutrition and unemployment. This requires appropriate mechanism, institutions, models and policies to facilitate the women to attain their full potential and, thereby, contributing to even development of all members of the society. India will have to make concerted efforts in improving agricultural linkages, women empowerment, health care, sanitation, drinking water, nutrition awareness, and education by adopting a convergence approach.